The Correlation Between Learning Styles, Language Learning Strategies, and English Learning Motivation of the Sixth Semester Students OF STIBA Persada Bunda - Barruansyah, Rauf Tetuko (Program Studi Pendidikan Bahasa Inggris FKIP UIR, 2018)
Abstract Motivation is an important thing in the classroom to make the learning runs well. By having good motivation, students will give more efforts to achieve their desired goal for example getting a good score. There are some factors  influence students’ motivation. Two of them are learning style and reading strategy use. Brown defines learning styles as the way in which someone’s perceive the information or knowledge in learning situation. It has to do with someone’s characteristic in learning. It can be visual, auditory, kinesthetic or etc. The learning style which belongs to someone can be different from one to each another. The way someone (student) in learning, might also have particular strategy that influence motivation especially in learning English. The students who are aware of applying language learning strategies will get a helpful way in learning the language. Learning strategies are specific actions taken by the learner to make learning easier, faster, more enjoyable, more self directed, more effective, and more transferable to new situations. In order to improve students’ motivation, pertinent questions about students’ learning styles and language learning strategy in learning English need to be addressed. The research was conducted in STIBA Persada Bunda. The instrument used in this research was Questionnaire. Based on the results, all of Alternative hypotheses were accepted. First hypothesis, there was a significant correlation between learning styles and students’ motivation in learning English. Second hypothesis, there was a significant correlation between language learning strategies and students’ motivation in learning English. And the third hypothesis, language learning strategy gave more influence than learning styles